Meta Analisis Model Pembelajaran Problem Based Learning dalam Meningkatkan Keterampilan Berpikir Kritis di Sekolah Dasar [A Meta-analysis of Problem-Based Learning Models in Increasing Critical Thinking Skills in Elementary Schools] - Indri Anugraheni (Universitas Pelita Harapan, 2018)
This study aims to analyze Problem-based Learning models intended to improve critical thinking skills in elementary school students. Problem-based learning models are learning processes where students are open minded, reflexive, active, reflective, and critical through real-world context activities. In this study the researcher used a meta-analysis method. First, the researcher formulated the research problem, then proceeded to review the existing relevant research for analysis. Data were collected by using a non-test technique by browsing electronic journals through Google Scholar and studying documentation in the library. Seven articles were found through Google Scholar and only one was found in the library. Based on the analysis of the results, the problem-based learning model can improve students' thinking ability from as little as 2.87% up to 33.56% with an average of 14.18%.BAHASA INDONESIA ABSTRAK: Penelitian ini bertujuan untuk menganalisis kembali tentang model pembelajaran Problem Based Learning untuk meningkatkan keterampilan berpikir kritis di Sekolah Dasar. Model pembelajaran Problem Based Learning adalah proses pembelajaran dimana siswa mampu memiliki pola pikir yang terbuka, refktif, aktif, reflektif dan kritis melalui kegiatan konteks dunia nyata. Dalam penelitian ini peneliti menggunakan metode meta analisis. Pertama-tama, peneliti merumuskan masalah penelitian, kemudian dilanjutkan dengan menelusuri penelitian yang sudah ada dan relevan untuk dianalisis. Teknik pengumpulan data dengan menggunakan non tes yaitu dengan menelusuri jurnal elektronik melalui google Cendekia dan studi dokumentasi di perpustakaan. Dari hasil penelusuran diperoleh 20 artikel dari jurnal dan 3 dari repository. Berdasarkan hasil analisis ternyata model pembelajaran Problem Based Learning mampu meningkatkan kemampuan berpikir Siswa mulai dari yang terendah 2,87% sampai yang tertinggi 33,56% dengan rata-rata 12,73%.